Strong association between malnutrition, inflammation, and depression in elderly patients. A new novel geriatric complex based on malnutrition; MID complex? Malnutrition, Inflammation and Depression in Elderly Patients - Turkbeyler, İbrahim Halil and Öztürk, Zeynel Abidin and Gol, Mehmet and Efendioglu, Eyüp Murat and Sahinbeyoglu, Seyma (Progress in Nutrition, 2020)
Background/Aim: The proportion of elderly individuals is increasing worldwide and geriatric syndromes (GS) are associated with a decreased life span. Malnutrition and depression are highly prevalent among the elderly and associated with poor clinical prognosis. This study investigated the frequency of inflammation and depressive symptom comorbidity in the context of a cause-and-effect relationship among elderly patients with malnutrition and/or malnutrition risk. Material and Methods: Participants in this cross-sectional study included 217 individuals aged 65 years and over. Comprehensive geriatric assessment was performed to participants. Malnutrition and depression were diagnosed according to the Mini-Nutritional Assessment (MNA-SF) Tool and Yesavage Geriatric Depression Scale (YGDS), respectively. Inflammation status were diagnosed according to the C-reactive protein (CRP) levels. Results: According to MNA-SF, 41 (18.9%) patients were malnourished, 82 (37.8%) at a risk of malnutrition, and 94 (43.3%) possessed normal nutrition. Among the malnourished patients, 51.2% experienced CRP elevation and 70.7% displayed symptoms of depression. Patients at risk of malnutrition experienced 39.0% CRP elevation, and 46.3% displayed depression symptoms. There was a statistically significant negative correlation between MNA-SF scores and YGDS and CRP (r: -0,201, p: 0,003, r: -0,495, p: 0,000, respectively). The incidence of inflammation-depression association in malnourished patients was 36.6%, 12.2% in those at risk for malnutrition, and 10.6% in those with normal nutrition. Conclusion: Physicians should be informed regarding the association among malnutrition, inflammation, and depression in geriatric patients.